Improved methodology for constructing and calculating the multidimensional human development index - Olga P. Kuznetsova, Anatoliy D. Kosmin,; Kosmina, Elena A. (Opción, 2019)
The paper objectives are to identify the drawbacks of the human development index and to propose ways of improving it. Historical-logical and morphological methods were used, as well as the modeling method of latent indices. In result, the main disadvantage of the complicated algorithm of the human development index consists in the fact that further widening of the components of the human development index will make the procedure of such calculation even more complicated. In conclusion, the model would better describe the actual level of human development in various countries and regions, under knowledge economy characterized by increased creative activity.